The Impact of Global Financial Crisis on IPO Underpricing in Malaysian Stock Market - Leow, Hon Wei; Lau, Wee Yeap (World Scientific Publishing, 2018)
This study examines the impact of the Global Financial Crisis (GFC) on Initial Public Offering (IPO) underpricing in the context of an emerging market from January 2006 to December 2011. Models consist of hierarchical and dummy variable regressions have been evaluated. Our results show, firstly, by comparison between the pre-GFC, GFC and post-GFC periods, it can be observed that IPOs initial returns (offer-to-close) are generally lower due to the crisis. Secondly, IPO underpricing provides an average of 17-25% of initial returns in the pre-GFC period, 1-3% during GFC period, and 3-7% in the post-GFC period. Thirdly, the financial crisis does not act as a moderator that worsens the relationship between underpricing of IPO and oversubscription ratio. Lastly, this study dispels the notion that investors should totally shun IPO during crisis period as there are still positive initial returns among the new issues. To the authors' knowledge, this is the first study on the impact of the GFC on IPO underpricing in Malaysia.